2022
DOI: 10.1371/journal.pone.0265107
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of central obesity and its associated risk factors among adults in Southeast Ethiopia: A community-based cross-sectional study

Abstract: Background Obesity and overweight are known public health problems that affect populations across the world. These conditions have been associated with a wide range of chronic diseases including type 2 diabetes mellitus, cardiovascular disease, and cancers. In Ethiopia, the literature regarding the burden of central (abdominal) obesity is scarce. This study aimed to fill this gap by assessing the prevalence and risk factors associated with central obesity among adults in Ethiopia. Methods From May to July 20… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 52 publications
1
4
2
Order By: Relevance
“…Our findings are similar to those of a study done in Tunisia (Traissac et al, 2015) which showed a much higher prevalence of abdominal than total obesity at 60% and 37% respectively in the same study population. On the contrary, studies measuring abdominal obesity using WC only in Southwest Iran and Southeast Ethiopia recorded a prevalence of 28.6% and 39.01% respectively, much lower than the prevalence from our study (Ghaderian et al, 2019), (Tekalegn et al, 2022).…”
Section: Discussioncontrasting
confidence: 97%
See 2 more Smart Citations
“…Our findings are similar to those of a study done in Tunisia (Traissac et al, 2015) which showed a much higher prevalence of abdominal than total obesity at 60% and 37% respectively in the same study population. On the contrary, studies measuring abdominal obesity using WC only in Southwest Iran and Southeast Ethiopia recorded a prevalence of 28.6% and 39.01% respectively, much lower than the prevalence from our study (Ghaderian et al, 2019), (Tekalegn et al, 2022).…”
Section: Discussioncontrasting
confidence: 97%
“…Similarly, studies conducted in Ethiopia revealed that respondents who were of a better economic status were more likely to be obese compared to those of low economic status [28,42].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…These findings are in line with the study done by (Mogeni & Ouma, 2022) who reported females embraced greater dietary diversity in their eating habits compared to males. The possible variations in the obesity prevalence could be justified by the use of different cutoff values for waist circumference (Tekalegn et al, 2022). Moreover, the findings of this study corroborate with (Molla et al, 2020)mthe odds of being centrally obese was 9.62 times higher among female study participants compared to their counterparts.…”
Section: Anthropometric Status Of University Students Central Obesity...supporting
confidence: 84%
“…This will be needed to decrease the incidence of metabolic risk factors before an overt metabolic disease (cardiovascular or diabetes) happens. A higher prevalence of central obesity (39%) was reported in southern Ethiopia [ 45 ].…”
Section: Discussionmentioning
confidence: 99%